2009
DOI: 10.1515/jpem.2009.22.7.581
|View full text |Cite
|
Sign up to set email alerts
|

Pleiotropic Genetic Syndromes with Developmental Abnormalities Associated with Obesity

Abstract: Childhood obesity is a common and complex problem that may persist in adulthood. It may present as a component of genetic syndromes associated with dysmorphic features, developmental abnormalities, mental retardation and/or learning disabilities and often neuroendocrine dysfunction. Although the chromosomal abnormalities of these rare syndromes are already known, the specific genetic and pathophysiological mechanisms leading to the distinct phenotypes and obesity still remain unclarified. New exciting genetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
8

Year Published

2010
2010
2016
2016

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 78 publications
0
6
0
8
Order By: Relevance
“…These mutations are all rare and lead, apart from extreme obesity with an early onset, to additional phenotypical manifestations, including red hair ( POMC ), reduced or impaired fertility ( PC1 , leptin and LEPR ), adrenal insufficiency ( POMC ), and impaired immunity ( LEP ) [16, 43, 65]. The pleiotropic effects warrant the consideration that these recessive disorders are classified as syndromal forms of obesity—similar to the Bardet–Biedl, Prader–Willi and other genetic syndromes associated with obesity [43, 66]. The pleiotropic Bardet–Biedl syndrome, of which obesity is one of the main clinical features, has been shown to have an oligogenic basis [14, 19, 43].…”
Section: Introductionmentioning
confidence: 99%
“…These mutations are all rare and lead, apart from extreme obesity with an early onset, to additional phenotypical manifestations, including red hair ( POMC ), reduced or impaired fertility ( PC1 , leptin and LEPR ), adrenal insufficiency ( POMC ), and impaired immunity ( LEP ) [16, 43, 65]. The pleiotropic effects warrant the consideration that these recessive disorders are classified as syndromal forms of obesity—similar to the Bardet–Biedl, Prader–Willi and other genetic syndromes associated with obesity [43, 66]. The pleiotropic Bardet–Biedl syndrome, of which obesity is one of the main clinical features, has been shown to have an oligogenic basis [14, 19, 43].…”
Section: Introductionmentioning
confidence: 99%
“…Cette pathologie est reconnue comme une maladie à transmission autosomique dominante mais secondaire au phénomène d'empreinte transmise par l'allèle paternel [5]. Le SPW est caractérisé par une hypotonie musculaire à la naissance, une hyperphagie et impulsivité alimentaire sévère, des troubles du comportement, des traits dysmorphiques, un retard mental, une obésité progressive, un hypogonadisme [6]. La cause moléculaire la plus commune des SPW est la suppression par délétion génomique ou par anomalie fonctionnelle d'une région chromosomique située sur le chromosome 15 (15q11.2-q12).…”
Section: Quelques Exemples D'obésités Génétiquesunclassified
“…Elle est caractérisée par une petite taille, une obésité, une brachydactylie, des malformations du crâne et de la face et parfois des anomalies du développement [6]. Ce syndrome associe une résistance à diverses hormones, dont une résistance à l'action de la parathormone.…”
Section: Ostéodystrophie Héréditaire D'albrightunclassified
See 1 more Smart Citation
“…Indeed, twin and adoption studies have revealed that heritability of obesity is about 40–70% [5, 6]; although it may be that current heritability estimates are inflated. Furthermore, there are a number of rare monogenic causes of obesity [7] and genetic syndromes that have obesity as a central feature [810], which in fact provided the first indications of how obesity development might be strongly influenced by genes.…”
Section: Introductionmentioning
confidence: 99%